China's food conundrum : insecurity of the rural abandoned - Zhang, Hongzhou (2012)
The 130 million people who are left behind in China’s rural areas are posing a severe challenge to the country’s food security -- for the food producers as much as consumers. The conundrum of the abandoned farmers and farmland may have global implications.